2011
DOI: 10.5032/jae.2011.02047
|View full text |Cite
|
Sign up to set email alerts
|

Value and Expectations of Supervised Agricultural Experiences as Expressed by Agriculture Instructors in Oklahoma Who were Alternatively Certified

Abstract: The purpose of this qualitative descriptive study was to determine the value and expectations for student participation in supervised agricultural experience (SAE) programs, as expressed by first-year, agricultural education teachers in Oklahoma who were alternatively certified. This study revealed that teachers in this study value the fact that the SAE program: (a) prepares students for future, possible careers by developing their skills for college and life beyond high school; (b) allows students to build re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 13 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…This conclusion was supported by the work of Roberts and Dyer (2004) and Terry and Briers (2010) who postulated teachers were expected to utilize SAE and to encourage students to participate in an SAE program. However, this study found SAE was one of the most difficult components of agricultural education to teach and implement with students, supporting Robinson and Haynes (2011).…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 53%
“…This conclusion was supported by the work of Roberts and Dyer (2004) and Terry and Briers (2010) who postulated teachers were expected to utilize SAE and to encourage students to participate in an SAE program. However, this study found SAE was one of the most difficult components of agricultural education to teach and implement with students, supporting Robinson and Haynes (2011).…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 53%
“…Teacher educators should provide the expert guidance to pre-service teachers regarding the skills and experiences they need to be successful in the classroom (Rubenstein & Thoron, 2015;Stair et al, 2012). Teachers have indicated that ensuring SAE quality and effectiveness is one of the most important and difficult tasks associated with teaching school-based agriculture (Dyer & Osborne, 1995;Ramsey & Edwards, 2012;Robinson & Haynes, 2011;Rubenstein et al, 2014). Therefore, including SAEs in teacher preparation programs is imperative (McLean & Camp, 2000).…”
Section: )mentioning
confidence: 99%
“…Consideration of Bandura's (1986) selfefficacy, and the respondents' perceptions of their competence in SAE task-specific competencies, beginning teachers should be successful in all areas SAE. However, previous studies indicated that SAE is a struggle and, at times, seen as unimportant in SBAE by practicing agriculture teachers (Dyer & Osborne, 1995;Robinson & Haynes, 2011).…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Research has indicated that teachers do not implement SAE programs as they conceptually and theoretically define SAE (Dyer & Osborne, 1995;Retallick, 2010;Wilson & Moore, 2007). Likewise, teachers have reported that teaching and utilizing SAE is one of the most difficult components to teaching agricultural education (Dyer & Osborne, 1995;Robinson & Haynes, 2011). One of the main teacher constraints to utilizing SAE programs is the inclusion of supervision for each student's SAE program (Osborne, 1988;Dyer & Osborne, 1995;Dyer & Williams, 1997;Swortzel, 1996).…”
mentioning
confidence: 99%